The new science of asset allocation : risk management in a multi-asset world - Schneeweis, Thomas; Crowder, Gary B. , 1954-; Kazemi, Hossein , 1954- (Wiley finance, 2010)
"The authors first focus on risk, examining the principles tools associated with quantitative and qualitative analysis in determining fundamental asset and portfolio risk, as well as the ability of money managers to create value. While pointing out the importance of manager discretion in the asset allocation process, they also present solutions, which emphasize systematic approaches to capturing expected returns while limiting downside risk. They provide illustrative examples of an investor's decision-making process in moving between and among core and satellite portfolios and offer an overview of sample allocations and expected risk/return scenarios."--BOOK JACKET